Efektivitas Besaran Dana Bantuan Hukum Litigasi terhadap Kebutuhan Pendampingan Hukum pada Proses Peradilan - M. Rizki Yudha Prawira (Jurnal Hukum Lex Generalis, 2025)
This research analyzes the effectiveness of litigation legal aid funding in Indonesia in ensuring equal access to justice, particularly for the poor and vulnerable. Findings show that real needs on the ground exceed the legal aid funding provided by the state. The gap between funding and actual legal aid costs may affect the quality of assistance delivered. In line with international human rights standards, this study emphasizes the urgency of reforming the funding scheme to be more adaptive and needs-based, ensuring that legal aid is delivered effectively, professionally, and equitably.